Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1590/0100-3984.2015.0209
|View full text |Cite
|
Sign up to set email alerts
|

Common and uncommon features of focal splenic lesions on contrast-enhanced ultrasound: a pictorial review

Abstract: The characterization of focal splenic lesions by ultrasound can be quite challenging. The recent introduction of contrast-enhanced ultrasound (CEUS) has come to play a valuable role in the field of imaging splenic pathologies, offering the possibility of an ionizing radiation-free investigation. Because CEUS has been incorporated into everyday clinical practice, malignant diseases such as focal lymphomatous infiltration, metastatic deposits, benign cysts, traumatic fractures, and hemangiomas can now be accurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Its employment did increase the sensitivity of US techniques for recognizing traumatic abdominal lesions. These reached levels of accuracy are quite similar to those obtained with CT (up to 95%) [10][11][12].…”
Section: Us-ceussupporting
confidence: 82%
“…Its employment did increase the sensitivity of US techniques for recognizing traumatic abdominal lesions. These reached levels of accuracy are quite similar to those obtained with CT (up to 95%) [10][11][12].…”
Section: Us-ceussupporting
confidence: 82%
“…CT Scan and MRI are imaging modalities that have very high sensitivity. Splenic abscess typically shows a thick irregular edge with hypodense in the middle, but multiple abscesses may be difficult to recognize (Krokos et al 2011, Zavariz et al 2017. In this case report, we presented a rare case about splenic abscess according to the literature.…”
Section: Discussionmentioning
confidence: 86%
“…This indicated that compared with conventional US and CDFI, CUES can more accurately and sensitively reflect the blood flow of the lesions. CEUS is a rapidly growing ultrasound technology that can visualize the low-speed blood flow and detect the perfusion characteristics in real time, thereby improving the diagnosis of splenic lesions [ 9 11 , 19 ]. Compared with contrast-enhanced computer tomography (CT) and contrast-enhanced magnetic resonance imaging (MRI), CEUS is a relatively safe, cost-effective, and time-saving technique.…”
Section: Discussionmentioning
confidence: 99%